Fabrication and characterization of hybrid perovskite thin films for solar cell application - Chen, Qing Hong (Nanyang Technological University, 2020)
Perovskite solar cells (PSCs) are one of the most promising photovoltaic technology in recent years, owing to the remarkable properties of perovskite such as high defect tolerance, long charge carrier lifetime, high absorption coefficient, etc. However, several bottlenecks are preventing this technology from being commercialised, which mainly concerns its long-term stability in outdoor environment. Defects present in the perovskite hinders the full potential of perovskite as an absorber in solar cell, and may accelerate certain degradations to occur. Passivation through additives has been shown to be a cheap and convenient way to eliminate or minimise defects. As such, we propose the use of triphenylphosphine sulphide (TPPS) as a passivating agent, which was introduced into perovskite through a novel method — as an additive in antisolvent. Results show that by modifying the perovskite with 1 mg/mL of TPPS, it shows the most improvement in terms of performance, where power conversion efficiency has on average increased by 7.55 % as compared to pristine devices, with the champion device having an efficiency of 14.8 %. Photoluminescence results proved that by incorporating TPPS into perovskite, less quenching occurs, which is an indication that trap states were successfully passivated. TPPS passivation may potentially aid in moisture and storage stability, yet test results were not fully indicative, thus more tests will be required. Although the mechanism behind TPPS passivation is yet fully understood, using it to passivate defects and improve the performance of PSCs seems promising.